2014
DOI: 10.3109/11038128.2014.894572
|View full text |Cite
|
Sign up to set email alerts
|

Work and everyday activities: Experiences from two interventions addressing people with common mental disorders

Abstract: According to the participants, experiences from both PBM and CBT had a positive impact on their ability to work and perform other everyday activities in a more sustainable way. Reflecting on behaviour and achieving limiting strategies were perceived as helpful in both interventions, although varying abilities to incorporate strategies were described. In general, the results support the use of active coping-developing interventions rather than passive treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 42 publications
1
28
0
Order By: Relevance
“…One explanation could, therefore, be that our study lacked an intervention with direct focus on the workplace. Further, Jansson et al showed that both problem-based self-care in a group and CBT had a positive impact on the patients’ ability to work 27. Imamura et al have shown a small effect of ICBT in increasing the work engagement in the general population 28.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One explanation could, therefore, be that our study lacked an intervention with direct focus on the workplace. Further, Jansson et al showed that both problem-based self-care in a group and CBT had a positive impact on the patients’ ability to work 27. Imamura et al have shown a small effect of ICBT in increasing the work engagement in the general population 28.…”
Section: Discussionmentioning
confidence: 99%
“…An important factor that was not currently measured is the patient’s own expectations of RTW after sick leave, which can be predictive of his/her actual return to work 27,44…”
Section: Discussionmentioning
confidence: 99%
“…a period of paid sick leave from work, often together with drug treatment without any active treatments enhancing the individual's own efforts for recovery [10,11].…”
Section: Mhp From the Perspective Of Health Carementioning
confidence: 99%
“…Hence, when the sick-listed workers in the current study perceived RTW adjustments as positive and useful, it is based on insights and reflections from the sick-listed worker, that were elicited, reflected, and summarized by the MI caseworker. Merely discussing their situation with MI caseworkers may also result in increased awareness of the sick-listed worker's own capacity, which, arguably, is a component of selfefficacy [44]. Norlund et al [45] state that self-efficacy, the belief in ones' ability to achieve a given goal or task, affects thought patterns that could be barriers to returning to work.…”
Section: Discussionmentioning
confidence: 99%